The Effect of Teacher Motivation Islamic Religious Education Towards Improving Student Learning Outcomes at MI Nurul Ilmi Nabire - Susi Siviana Sari; Nurichsan Nurichsan (Edunesia: Jurnal Ilmiah Pendidikan, 2021)
The purpose of this study was to determine: motivation for teachers of islamic religious education at MI Nurul Ilmi Nabire, increasing learning of students at MI Nurul Ilmi Nabire, the effect of motivation for islamic religious education teachers on improving student learning outcomes in MI Nurul Ilmi Nabire. The method used is quantitative research with survey methods. The population was students at MI Nurul Ilmi Nabire with a sample of 30 people. Data obtained through questionnaires, interviews and observations. The results are then analyzed in a correlational manner which is presented in tabular form. Based on the results of the calculation of the product moment correlation with the help of SPSS version 16.0 where to find out each variable has a directional correlation of the two variables, namely the X variable and the Y variable, which indicates that motivation by the teacher has a correlation coefficient value of 0.479 (47.9%). While the results of the F-test are indicated by the value of Fcount (0.198) <Ftable (0.113) with a significance value of 0.660 > 0.05, which means that it is greater than 0.05. And the t-test results that get the value of tcount -445 < ttable 1.120 with a significance level of 0.660 > 0.05. This shows that the value of Sig. 0.05 has failed, because the results of both F and t is greater than 0.05. So it can be concluded that Ho is accepted and Ha is rejected.